Principles of Canadian income tax law - Li, Jinyan (Thomson Reuters, 2022)
"Dedicated to Peter Hogg, Principles of Canadian Income Tax Law, 10th Edition elucidates Canadian income tax law in simple, concise, and non-technical language. The book encourages us to think deeply and critically about the important role of income tax in Canadian society.It emphasizes the principles of income tax law, the policies that influence and underlie the system, and its major features and context. The book upholds tax law as a rational system contributing to Canadas socio-economic fabric. Income tax is the main instrument for financing and sharing among Canadians the cost of collective consumption of goods and services and expressing notions of social welfare, distributive justice, and political civility." –Publisher.